2017
DOI: 10.1186/s12913-017-2154-y
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking specialty hospitals, a scoping review on theory and practice

Abstract: BackgroundAlthough benchmarking may improve hospital processes, research on this subject is limited. The aim of this study was to provide an overview of publications on benchmarking in specialty hospitals and a description of study characteristics.MethodsWe searched PubMed and EMBASE for articles published in English in the last 10 years. Eligible articles described a project stating benchmarking as its objective and involving a specialty hospital or specific patient category; or those dealing with the methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…Accessed 31/05/ 2019), aims to provide a means of comparing clinical performance with the wider dataset. Benchmarking has become mandatory in a number of countries for a range of medical and surgical procedures and is used by competent authorities, regulators and payers for quality assurance of clinical effectiveness, safety and cost-effectiveness of patient care [1][2][3][4][5][6][7]. However, there are challenges in the delivery of benchmarking, particularly in defining a fair, accurate and clinically meaningful methodology acceptable to all stakeholders underpinned by a reliable and complete source of clinical outcomes data.…”
Section: Introduction Aims and Objectivesmentioning
confidence: 99%
“…Accessed 31/05/ 2019), aims to provide a means of comparing clinical performance with the wider dataset. Benchmarking has become mandatory in a number of countries for a range of medical and surgical procedures and is used by competent authorities, regulators and payers for quality assurance of clinical effectiveness, safety and cost-effectiveness of patient care [1][2][3][4][5][6][7]. However, there are challenges in the delivery of benchmarking, particularly in defining a fair, accurate and clinically meaningful methodology acceptable to all stakeholders underpinned by a reliable and complete source of clinical outcomes data.…”
Section: Introduction Aims and Objectivesmentioning
confidence: 99%
“…This tool has been shown to be efficient when there is a need to analyze established metrics to improve practices and modify processes to provide more reliable decision making (43) . In contrast, a review on the effectiveness of benchmarking to improve quality in specialized hospitals has shown promising effects, however more robust and structured actions are needed for the use of the tool (44) .…”
Section: Tools For Monitoring Resultsmentioning
confidence: 99%
“…As mentioned, the mission of the Results Centre is to measure, evaluate and disseminate the results that are gathered in field of health care by the different players in the all‐embracing public health system in Catalonia in order to promote benchmarking among centres and transparency towards society. Furthermore, it has been shown that comparison between health care centres contributes to an enhancement in outcomes and also to an important saving by improving the adequacy of procedures (Larsson et al., 2012; Wind & Van Harten, 2017). After having been established and developed over 7 years, the Results Centre has now become a reference tool in the Catalan health care system.…”
Section: Discussionmentioning
confidence: 99%